Unveiling Specific Business Strategy for Improvement in Enterprise’s Performance in Sokoto State: Evidence from Small and Medium Enterprises - Nafiu, Akeem Tunde; Ogamenyi, Ogamenyi Iga; Otohinoyi, Ozovehe (Acta Universitatis Danubius. Œconomica, 2022)
This study aimed at unveiling specific business strategy for improvement in enterprise’s performance in Sokoto State. The survey research design was applied. A multi-stage sampling technique was used to choose the sample of 206. The data generated for the study was analyzed using both descriptive statistics and regression analysis. Finding revealed that cost-leadership strategy has significant effect on the profitability of SMEs in Sokoto State, and that differentiation strategy has significant effects on the market share of SMEs in Sokoto State. The study concluded that cost-leadership strategy and differentiation strategy are keys to strategic management. The study recommended that SME owner/managers should commit less resource to cost-leadership strategy so as to achieve increased profitability in Sokoto State, and they should increase their effort towards the adoption of effective differentiation strategy as it will increase their market share at the long run in Sokoto State.